Neurofibromatosis of head of pancreas: Obstructive jaundice - Fronzutti, Agustín; Lorenzelli, Amílcar; Segal, Marcos; Rieppi, Leo; Rodríguez De Vecchi, Victoriano (Cirugía del Uruguay, 1978)
A 43-year-old patient from the provinces was suffering from Recklinghausen's disease with a 2-monthevolution cold obstructive jaundice. Paraclinic preoperative exploration showed complete biliary extrahepatic obstruction and considerable dilatation of intrahepatic biliary tract clearly shown by studies performed by conventional scintillogTaphic methods and by Bengal Rose. These methods of study are of considerable importance. Surgical e.xploration showed a tumor in the head of the pancreas which compressed the intra pancreatic biliary duct and diffuse peritoneal tumoral formations which histol'ogy defines as Neurofibromas. Cholecystojejunostomy was performed and immediate evolution was good, distant results are unknown. The papercontains a review of literature which indicates how rare this location is, since ours seems to be the first case of pancreatic location with obstructive jaundice. There follows a discussion of evolutive possibilities of this disease, with special emphasis on the risk of its becoming malign; the conclusion is that whenever possible the ideal treatment in such cases is ressection.